On The Demand Of Electric Vehicles In Malaysia And Its Potential, Statistical Analysis - Suhaimi, Saiful Anwar (Universiti Sains Malaysia, 2021)
Electric vehicles exist since the early 20th century, however only around 5% of current vehicles globally are powered by an electric drivetrain or a hybrid of an electric drivetrain. Vehicles which uses internal combustion engines (ICE) are deemed outdated; they have low efficiency, consume a lot of fuel and produce harmful emissions. However, the general population still prefer ICE vehicles because they are more accessible, generally cheaper and the electric vehicle infrastructure is very primitive which means that they are still inaccessible to the majority of the general population. Limited EV infrastructures such as charging stations are one of the main reasons why EVs are not the main transportation system in our society today. Therefore, this study aims to mainly determine the demand and potential of electric vehicles in the global market. This study will further expand upon the advantages as well as disadvantages of electric vehicles in comparison to vehicles using internal combustion engines. This study will be compiling data from various governmental bodies, both international and local, this study aims to predict the growth of the electric vehicle sector in the near future. Moreover this study also aims to properly determine the emmissions that will be removed if the general population start to transition into using electric vehicles. Using an external simulation software such as Simulink, this study is able to create a predictive model that maps out the electric vehicle stock and sales, as well as oil displacement and CO2 emission equivalence in lieu of using electric vehicles as to using internal combustion engines.